Menolak Buah dari Pohon Beracun: Pengaturan Exclusionary Rule dalam Hukum Acara Pidana Indonesia Berdasarkan Perspektif Fair Trial - M. Rizki Yudha Prawira; Shahinshah Satria Al Aziz (Esensi Hukum, 2025)
The enactment of Law Number 20 of 2025 on the Criminal Procedure Code introduces an improvement to Indonesian criminal evidence law by explicitly recognizing the exclusionary rule in Article 235. Unlike the 1981 Criminal Procedure Code, which merely enumerated categories of evidence without questioning the legality of their acquisition, the new provision establishes procedural legality as a precondition for the admissibility of evidence. This study aims to analyze the regulation of the exclusionary rule under Article 235 and to examine its opportunities and challenges from the perspectives of human rights and the right to a fair trial. The issues discussed include the concepts of illegally obtained evidence and the exclusionary rule, a comparison between the 1981 Code and the new Code, and a review against international human rights instruments. This research employs a normative legal method, using statutory and comparative approaches and drawing on the International Covenant on Civil and Political Rights (ICCPR) dan Convention Against Torture (CAT). The findings show that Article 235 strengthens human rights and fair trial guarantees, affirms the absolute exclusion of evidence obtained through torture, and restores equality of arms. Nevertheless, the provision has shortcomings, namely the absence of explicit regulation of the fruit of the poisonous tree doctrine, the good-faith exception, standing, and the burden of proof. The study recommends reinforcement through supreme court jurisprudence, implementing regulations, and the transformation of law enforcement working culture.